2017
DOI: 10.1038/ni1017-1173b
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Corrigendum: S100-alarmin-induced innate immune programming protects newborn infants from sepsis

Abstract: In the version of this article initially published online, the labels identifying each plot in Figure 1b In the version of this article initially published online, the flow cytometric dots were missing in the middle plot of the leftmost column in Figure 2f. The error has been corrected in the print, PDF and HTML versions of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…However, this concept is challenged by clinical observations of hyper-inflammatory courses of neonatal sepsis 42 . Recent work suggested that neonatal immune responses are not impaired, but rather determined by a tightly regulated physiological immune programming preventing harmful hyper-inflammation in combination with sufficient immunological protection 43 . The potency of the neonatal immune system to elicit a strong reaction to dangerous stimuli is also demonstrated by the fact that neonatal peripheral immune cells participate in sterile tissue inflammation induced by perinatal brain injury 44 , indicating a complex interplay between the peripheral immune and the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…However, this concept is challenged by clinical observations of hyper-inflammatory courses of neonatal sepsis 42 . Recent work suggested that neonatal immune responses are not impaired, but rather determined by a tightly regulated physiological immune programming preventing harmful hyper-inflammation in combination with sufficient immunological protection 43 . The potency of the neonatal immune system to elicit a strong reaction to dangerous stimuli is also demonstrated by the fact that neonatal peripheral immune cells participate in sterile tissue inflammation induced by perinatal brain injury 44 , indicating a complex interplay between the peripheral immune and the central nervous system.…”
Section: Introductionmentioning
confidence: 99%